Spontaneous scalarization in scalar–tensor theories with conformal symmetry as an attractor - Chiba, Takeshi (Progress of theoretical and experimental physics, 2022)
Abstract Motivated by constant-G theory, we introduce a one-parameter family of scalar–tensor theories as an extension of constant-G theory in which the conformal symmetry is a cosmological attractor. Since the model has the coupling function of negative curvature, we expect spontaneous scalarization to occur and that the parameter can be constrained by pulsar timing measurements. Modeling neutron stars with realistic equations of state, we study the structure of neutron stars and calculate the effective scalar coupling with the neutron star in these theories. We find that within the parameter region where the observational constraints are satisfied, the effective scalar coupling almost coincides with that derived using the quadratic model with the same curvature. This indicates that the constraints obtained by the quadratic model will be used to limit the curvature of the coupling function universally in the future.